Pemberdayaan Masyarakat Bekasi Timur Melalui Budi Daya UMKM Usaha Ikan Lele - Ari Soeti Yani; Kustiadi Basuki; Imam Suryono (Jurnal Pemberdayaan Nusantara, 2023)
This Community Service Program aims to determine the Empowerment of the East Bekasi community through Cultivating MSME in the Catfish Business Bekasi so that it is right on target. Catfish is a favorite food in Indonesia and is a factor that needs to be considered in view of the large number of people who consume catfish, the amount in the market, the proximity to raw materials, the availability of facilities and transportation costs and the availability of places to expand their business. While its special use for the people of East Bekasi is to increase the nutrition of the surrounding community so they don't experience malnutrition and so on. Frequent consumption of fish can improve thinking for the better, especially for children who are in their infancy. Clean catfish farm locations increase sales profits and attract more buyers to shop for catfish. While the benefits for partners are getting a work partner, in addition to this what the lecturer gets adds new insights that will be used in further learning about entrepreneurship.